1993
DOI: 10.1111/j.1360-0443.1993.tb02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in the European Community: uniformity and diversity in drinking patterns

Abstract: Within the European Community (EC) drinking patterns in the southern countries can be characterised by daily consumption of wine at meals, and in the northern countries by less frequent consumption of beer outside meals. Yet, as in past decades in the southern countries beer consumption and in the northern countries wine consumption strongly increased, the question is whether the distinction in drinking patterns still applies. This paper (1) describes for each country of the EC total alcohol consumption, (2) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
76
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 4 publications
7
76
1
2
Order By: Relevance
“…The European Community study 1 found that the frequency of wine consumption by women was much lower than that of men in the countries of southern Europe. This is mirrored by our finding that women consumed much less total ethanol than men in the Mediterranean countries, whereas in central and northern Europe, the total ethanol consumption of women was not far behind that of men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The European Community study 1 found that the frequency of wine consumption by women was much lower than that of men in the countries of southern Europe. This is mirrored by our finding that women consumed much less total ethanol than men in the Mediterranean countries, whereas in central and northern Europe, the total ethanol consumption of women was not far behind that of men.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, which evaluated the frequency of alcohol drinking, the Mediterranean countries were characterised mainly by wine consumption, whereas people in northern Europe mainly drank beer 1 . In our study this was only really true for men, since, for all study centres except Murcia (Spain), wine contributed more to women's total alcohol intake than all other sources combined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the introduction of the potato, beer was a major source of nourishment for central and northern Europe, with 'beer soup' being consumed for breakfast (Schivelbusch 1993: 22). However, even this north-south distinction is becoming blurred, as wine consumption increases in northern Europe and beer consumption rises in Mediterranean countries (Hupkens et al 1993).…”
mentioning
confidence: 99%